The Role of Self-Resilience and Self-Efficacy to Increase Adversity Quotient - Yesi Apriyani; Muhamad Uyun (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
Migrant students strive to achieve success with quality education. Some overseas students are afraid of facing difficulties, fear failure, and fear of not being able to adjust to existing associations, so they do not trust themselves and prefer to entrust others to overcome the challenges they face. Today's migrant students need resilience and high self-efficacy to adjust to changes in habits in a new environment. Resilience, Self-Efficacy, and Adversity Quotient are essential for individuals to develop the abilities that exist within overseas students. This study aimed to prove the correlation between Resilience and Self Efficacy with Adversity Quotient. Research subjects are active students of the Faculty of Psychology. The method used in this research is the quantitative method. Sampling using Purposive Random Sampling of as many as 205 subjects. Data were collected using measuring instruments in the form of a Self-Resilience scale, Self-Efficacy scale, and Adversity Quotient scale in the form of google form. Data analysis using multiple regression. The practical contribution given by the Resilience and Self Efficacy variables with Adversity Quotient is 30.4%, while other variables influence the remaining 69.6%. The results of data analysis show that Resilience and Self Efficacy play a role in increasing Adversity Quotient with a significant value of p=0.000 (0.001 <0.05). The results showed that the higher the Resilience and Self Efficacy, the higher the level of Adversity Quotient.Mahasiswa perantau berusaha untuk menggapai kesuksesan dengan pendidikan yang berkualitas. Beberapa mahasiswa perantau takut menghadapi kesulitan sendiri, takut akan kegagalan, takut tidak mampu menyesuaikan pergaulan yang ada, sehingga tidak percaya diri dan lebih memilih mempercayakan orang lain untuk mengatasi tantangan yang dihadapi. Mahasiswa perantau saat ini membutuhkan Ketahanan Diri dan keyakinan diri yang tinggi untuk menyesuaikan perubahan kebiasaan dilingkungan baru. Ketahanan Diri, Self Efficacy, dan Adversity Quotient adalah hal yang penting bagi individu untuk mengembangkan kemampuan yang ada dalam diri mahasiswa perantau. Tujuan penelitian ini adalah untuk membuktikan korelasi antara Ketahanan Diri dan Self Efficacy dengan Adversity Quotient. Subjek penelitian Mahasiswa aktif Fakultas Psikologi. Metode yang digunakan dalam penelitian ini yaitu metode kuantitatif. Pengambilan sampel menggunakan Purposive Random Sampling sebanyak 205 subjek. Data dikumpulkan menggunakan alat ukur berupa skala Ketahanan Diri, skala Self Efficacy dan skala Adversity Quotient dalam bentuk google form. Analisis data menggunakan regresi berganda. Sumbangan efektif yang diberikan variabel Ketahanan Diri dan Self Efficacy dengan Adversity Quotient yaitu sebesar 30,4%, sedangkan selebihnya sebesar 69,6% dipengaruhi oleh variabel lain. Hasil analisis data menunjukan bahwa Ketahanan Diri dan Self Efficacy berperan meningkatkan Adversity Quotient dengan nilai signifikan p=0,000 (0,001 < 0,05). Hasil penelitian menunjukkan bahwa jika semakin tinggi Ketahanan Diri dan Self Efficacy maka semakin tinggi tingkat Adversity Quotient.